Attitude towards the habit of reading in young people of 10th grade of the INSEAQ - Álvarez Mosquera, Rommel; Mosquera Torres, Yucy; Redondo Mendoza, Ciro Ernesto (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The present study intends to describe the most frequent attitudes that high school students show towards reading and the factors that affect their liking or dislike for it, since it is of vital importance to be able to know and discover the difficulties that students may have. in their reading process, since an early knowledge of those difficulties makes it possible to prevent specific learning difficulties, fears or disorders of reading habits. The study was carried out through observation and individual interviews that inquired about reading in discourse and reading in practice.